De l'obéissance à la révolte ? - Diana Martins (Medievalista)
The rebellion of the heir to the Portuguese crown, Afonso, against his father, King Dinis of Portugal (1279-1325), between 1317 and 1323, had a profound influence on the perception we have of the relationship that existed between the sovereign and his heir and successor. The aim of the present essay is to circumvent the occasional limitations imposed by the available sources and adopt a broader approach, taking the Prince's perspective as the starting point whilst seeking to understand, through various testimonies, the manner in which the successor was involved in his father's diplomatic efforts. In so doing, we seek to retrace the different phases of this relationship, while at the same time attempting to highlight instances when the Prince was able to act independently, that is, when his actions were neither conditioned nor regulated by his father's interests.